2006
DOI: 10.1530/eje.1.02292
|View full text |Cite
|
Sign up to set email alerts
|

Associations of remission status and lanreotide treatment with quality of life in patients with treated acromegaly

Abstract: Objective: Acromegaly has an important impact on quality of life (QOL). The aim of this study was to evaluate the associations of remission status and lanreotide treatment with QOL in patients with treated acromegaly, by the newly developed disease-generated acromegaly QOL questionnaire (ACROQOL). Design: Cross-sectional study. Methods: Fifty-two patients with treated acromegaly were recruited to complete the Chinese version of the ACROQOL translated and validated from the English version. These patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 23 publications
(19 reference statements)
7
51
2
Order By: Relevance
“…Several studies showed that QoL is severely affected in acromegalic patients, even in those patients with controlled disease [24][25][26][27][28]. In our study, the median AcroQoL total score seems quite low compared to other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Several studies showed that QoL is severely affected in acromegalic patients, even in those patients with controlled disease [24][25][26][27][28]. In our study, the median AcroQoL total score seems quite low compared to other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Further, our study did not rely only on the disease-specific AcroQoL but also on generic scales measuring HR-QoL and fatigue. A previous study by Hua et al (20) showed that in the group of patients with disease control, treatment with Lanreotide was associated with worse AcroQoL scores. This study was small, comparing 13 patients on Lanreotide treatment with 17 patients with cure of disease.…”
Section: Discussionmentioning
confidence: 95%
“…All acromegalic patients treated by long-acting forms of somatostatin analogs had monthly injections done by nurses of their neighborhood. Recently, a crosssectional study including 52 patients with treated acromegaly showed no difference in the AcroQol scores between controlled and uncontrolled groups (28). However, in the biochemically controlled group, patients treated with i.m.…”
Section: Discussionmentioning
confidence: 98%